The Effect of Health Promotion Using Motion Graphic Video Media on Mothers' Knowledge Regarding Early Detection of Toddler Growth and Development - Yulyanti Lubis, Rani; Aziza, Nurul; Yulia Maritasari, Dwi (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Mothers' lack of knowledge about child development disorders in Indonesia reaches approximately 7.51% of the population. Based on the results of the 2022 SSGI (Student Health Survey), growth and development problems in West Lampung Regency reached 16.6% of toddlers, and in 2024, eight toddlers were recorded with growth and development problems at the Sekincau Community Health Center. This is due to mothers' inadequate knowledge and skills regarding early detection of growth and development. The impact of this lack of knowledge on early detection of growth and development can result in deviations in growth, development, and mental and emotional well-being. Motion graphic media is an effective approach to health promotion, particularly in the context of counseling on early detection of toddler growth and development. The purpose of this study was to determine the effect of health promotion using motion graphic video media on mothers' knowledge regarding early detection of toddler growth and development, according to the minimum standards of the integrated health service post (Posyandu) in Giham, Sukamaju Hamlet. The results of the study showed that there was an increase in the average score of maternal knowledge in the pre-test of 41.25 with a standard deviation of 8.814 while the average score in the post-test was 78.19 with a standard deviation of 8.380. The results of the statistical analysis showed a significant average difference between the Pre-Test and Post-Test scores of maternal knowledge with a significance value of p-value 0.000 which means the p-value <0.05 which indicates the effectiveness of using motion graphic video media in increasing maternal knowledge. The suggestion of this study is that motion graphic media is effective for use as a health promotion medium.